Analisis Pemanfaatan Key Opinion Leader (KOL) oleh Batagor Acan sebagai Strategi Marketing Public Relations (MPR) di Instagram - Niantiara, Aulialukita (Jurnal Representamen, 2022)
A Key Opinion Leader (KOL) is someone who has the ability to persuade a group of people with knowledge and communication messages. The existence of this KOL is used by brands in improving marketing and public relations. This is crucial for the development of businesses that currently use social media a lot as a means of brand promotion. Therefore, the purpose of this study is to describe the use of KOL for Marketing Public Relations strategies on social media, especially on Instagram. This study will examine the theories of KOL itself as well as the theory of marketing public relations and analyze the strategy with KOL Specialists to determine its effectiveness. This study uses a qualitative method with interview data collection techniques. The results of this study indicate that the KOL strategy chosen by Batagor Acan has been effective with a significant impact in terms of sales and brand awareness, by taking 2 considerations as one way to choose the right KOL: active followers and the message. In addition, using the ideal form of KOL cooperation for culinary brands such as the distribution of discount coupons and customer testimonials to be able to detect KOL’s performance. Keywords: key opinion leader, marketing public relations, social media, Batagor Acan